Income diversification in enhancing food security among rural households in Nigeria - Muhammad, Muhammad Sani (2015)
Food security is now fundamental to the development policies of Nigeria. The country is faced with a challenge of feeding its ever-increasing population. Even though, Nigeria is a rich country with abundant natural and human resources, overwhelmingly large segment of its citizens are food insecure in both urban and rural communities. Studies have shown that most of the socioeconomic indicators for the country are very low. The food insecurity indices in Nigeria keep increasing with passage of time, for example, only 18 percent Nigeria population were food insecure in 1986, but the figure rose to 40 percent in 2005 and over 70 percent in 2013. This could be due to fact that, rural areas where most of the agricultural productions take place suffered many years of neglect; rural households were deprived of basic social infrastructure such as electricity, portable drinking water, heath care and educational facilities. Many rural communities are still not connected urban centres. Discovery of oil in Nigeria also led to the neglect of agricultural sector, hence recent increase in imports bills. Successive governments in Nigeria have failed to diversify the country’s economy away from oil sector. Due to the failure of the agricultural sector to occupy its rightful place in the Nigerian economy and its increase inability to provide the needed livelihoods to the rural households, the smallholder farmers adopt to diversify their portfolios away from agriculture. The diversification is seen as not only key to consumption smoothing but as a strategy to deal with different shocks. A nationally representative sample of 3372 rural households from General Household Survey-panel data that adopt the World Bank Living Standard Measurement Survey (LSMS) technique was used for this study. Based on 2120 kcal Food and Agricultural Organization (FAO) recommended per adult equivalent and 0.87 USD purchasing power parity (PPP), an annual food poverty threshold of (N50, 331.67) equivalent to 317.55 USD per annum was derived for Nigeria. This threshold is the cost for purchasing recommended daily food allowances (RDA) of an adult equivalent for healthy life in rural Nigeria. Chi-square analysis and t-test revealed that diversified households were relatively more food secure than undiversified at 0.05 per cent level of significance. The food security situation in Nigeria was examined using the Foster Greer and Thorbecke (FGT) class of decomposable food poverty measures that satisfy both monotonicity and transfer axioms. The coefficient of ∝, 0, 1 & 2 measures the incidence, depth and severity of food insecurity. The food insecurity indices at national level as measured by ∝ (∝=0, ∝=1 and ∝=2 measure the incidence, depth and severity of food insecurity respectively) shows that (∝=0, 46.36, ∝=1, 0.43 and ∝=2, 1.11 for and ∝=0, 42.78, ∝=1, 0.348 and ∝=2, 7.45) for post-harvest seasons respectively. This implies that almost half of the rural households in Nigeria are food insecure subsisting on less the RDAs, however, depth and severity of food insecurity also differ. The results of econometric analysis using logistic regression model revealed that the age of the household head, education up to tertiary level, household size, the value of the household’s livestock holdings, participation in non-farm enterprise, access to formal credit, distance to the urban centres and total remittances received by a household had statistically significant influence on food security. We conjecture that, the higher incidence of food insecurity during post harvesting season might likely be due to inability of smallholder farmers to utilize their time into non-farm income generating activities due to high demand for labour for farm operations. The results PSM suggested that on the average food consumption expenditure of the non-diversified households were less than that of participating households, and therefore more likely to be less food secure. Overall, the average increase in food expenditure due to diversification into non-farm income generating activities ranges between N1571.52 (10 USD) to N11654.07 (73.53 USD). The study recommends public policy initiatives that ensure credit availability, access to road, portable water, extension services and skill acquisition in rural areas as vital for ensuring food security and as well as encourage participation into non-farm sector. Further studies for panel data analysis was recommended using subsequent GHS. Subsequent panel waves could be adopted to look at the dynamics of food security over time. The study concludes that, variation in food exist between post-plant and post-harvesting seasons in Nigeria, diversification into non-farm activities has a positive impact on food security and food consumption expenditure in rural Nigeria.